Surgical Management of a Severe Early Implant Complication: A 19‐Year Follow‐Up Case Report. Issue 4 (1st November 2016) - Hamdan, Nader; Batista, Felipe Correa; Batista, Eraldo L.
Abstract : Introduction: Reports on long‐term response to treatment of different implant complications with a span of more than 15 years are scarce. This case report presents a patient with early severe bone loss around an unloaded dental implant, with treatment and 19‐year follow up. Case Presentation: A 60‐year‐old male non‐smoker with no known systemic contributory history presented for replacement of the mandibular right first molar. The tooth was replaced with a titanium plasma‐sprayed (TPS) implant using a non‐submerged healing approach. Eight weeks post‐surgery the patient reported discomfort in the area, followed by swelling, suppuration, and deep probing depths (PDs). A full‐thickness flap revealed a bone defect that was thoroughly debrided until its deepest extension. The implant surface was scaled and subjected to air‐powder treatment, followed by rubbing the TPS surface with a cotton pellet soaked in HCl‐tetracycline. Guided bone regeneration was accomplished with use of an allograft followed by placement of a non‐resorbable membrane. Follow‐up after 19 years showed stability of the bone gain and reduction of PDs. Conclusion: The 19‐year successful long‐term result calls attention to the potential benefit of the combined anti‐infective/regenerative approach and lasting effects of surgical management of early implant complications.